The impact of information security initiatives on supply chain robustness and performance: an empirical study - Sindhuja, P N (Information and computer security, 2021)
PurposeInformation security is an essential element in all business activities. The damage to businesses from information security breaches has become pervasive. The scope of information security has widened as information has become a critical supply chain asset, making it more important to protect the organization’s data. Today’s global supply chains rely upon the speedy and robust dissemination of information among supply chain partners. Hence, processing of accurate supply chain information is quintessential to ensure the robustness and performance of supply chains. An effective information security management (ISM) is deemed to ensure the robustness of supply chains. The purpose of the paper is to examine the impact of information security initiatives on supply chain robustness and performance.Design/methodology/approachBased on extant literature, a research model was developed and validated using a questionnaire survey instrument administered among information systems/information technology managers. Data collected were analyzed using exploratory and confirmatory factor analysis. Further, to test the hypotheses and to fit the theoretical model, Structural equation modeling techniques were used.FindingsResults of this study indicated that information security initiatives are positively associated with supply chain robustness and performance. These initiatives are likely to enhance the robustness and performance of the supply chains.Originality/valueWith the advancements in internet technologies and capabilities as well as considering the dynamic environment of supply chains, this study is relevant in terms of the capability that an organization needs to acquire with regards to ISM. Benefiting from the resource dependency theory, information security initiatives could be considered as a critical resource having an influence on the internal and external environment of supply chains.